Toxicity Characteristic Leaching Procedure and Iron Treatment of Brass Foundry Waste - Kendall, Douglas S (Environmental science & technology, 2003)
The Toxicity Characteristic Leaching Procedure (TCLP) is used by the United States Environmental Protection Agency to determine if wastes contain extractable components subject to hazardous waste regulations. This paper examines the limitations of the TCLP and the way it is used by studying a particular example. Waste casting sand from brass foundries to which iron metal has been added passes the TCLP test but when placed in a landfill for several years may start to leach lead, copper, and zinc. Results of TCLP tests of waste sand alone and with the additives iron metal, zinc metal, hydrous ferric oxide, and hematite are reported. Three processes were studied:  reduction by metallic iron, sorption by hydrous ferric oxide, and precipitation of hydroxides. Lead, copper, and zinc behave differently with respect to these three processes, and their measurement allows some deductions as to what is occurring in a TCLP test or a landfill. Iron addition does not result in long-term stabilization of a waste placed in the ground. The chemistry of a laboratory extraction can be very different from the chemistry of a waste placed in the environment. Wastes that are treated to pass the TCLP test, but are not permanently stabilized, are a threat to the environment.